Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/infa.12003
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Emotion Regulation Across Infancy: Do Age and the Social Partner Influence Temporal Patterns

Abstract: The ability to effectively regulate emotions is a critical component of early socio-emotional development. This longitudinal study examined the developmental trajectories of emotion regulation in a sample of 3-, 5-, and 7-month-olds during an interaction with mothers and fathers. Infants’ negative affect and use of behavioral strategies, including distraction, self-soothing, and high intensity motor behaviors were rated during the still-face episode of the Still-Face Paradigm. Longitudinal mixed-effects models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 30 publications
(75 reference statements)
5
48
1
Order By: Relevance
“…Previous work stemming from these data include three publications examining attachment but not infant SFP responses (Lickenbrock, Braungart-Rieker, Ekas, Zentall, Oshio, & Planalp, in press; Planalp & Braungart-Rieker, 2013; and Zentall, Braungart-Rieker, Ekas, & Lickenbrock, 2012), one examining second-by-second associations between affective and behavioral responses within the SFP but not attachment (Ekas, Lickenbrock, & Braungart-Rieker, 2013), and two looking neither at attachment nor infant SFP responses (Ekas, Braungart-Rieker, Lickenbrock, Zentall, & Maxwell, 2011; Planalp, Braungart-Rieker, Lickenbrock, & Zentall, S. (in press). For the purposes of this study, data from all but the last visit were examined.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work stemming from these data include three publications examining attachment but not infant SFP responses (Lickenbrock, Braungart-Rieker, Ekas, Zentall, Oshio, & Planalp, in press; Planalp & Braungart-Rieker, 2013; and Zentall, Braungart-Rieker, Ekas, & Lickenbrock, 2012), one examining second-by-second associations between affective and behavioral responses within the SFP but not attachment (Ekas, Lickenbrock, & Braungart-Rieker, 2013), and two looking neither at attachment nor infant SFP responses (Ekas, Braungart-Rieker, Lickenbrock, Zentall, & Maxwell, 2011; Planalp, Braungart-Rieker, Lickenbrock, & Zentall, S. (in press). For the purposes of this study, data from all but the last visit were examined.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these two regulatory behaviors (self‐comforting and self‐distraction) have been found to decrease infant negative affect during laboratory tasks. Specifically, using the same sample as the current study, Ekas et al () found that an infants’ use of self‐comforting and self‐distraction can lessen the amount of distress they exhibit. They found that negative affect during the still‐face episode of the SFP decreased within three‐seconds of the use of those regulatory strategies.…”
mentioning
confidence: 91%
“…Two behavioral regulation strategies have been empirically supported as regulatory where the occurrence of the behavior relieves negative arousal (Ekas, Lickenbrock, & Braungart‐Rieker, ). Infants use self‐comforting behaviors, such as lip smacking or thumb sucking, to regulate arousal (Stifter & Braungart, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When the caregiver is uncharacteristically unresponsive, the infant must attempt to self-regulate. When either mothers or fathers were instructed to be unresponsive, 3 to7-month-olds employed similar strategies to regulate their emotions (e.g., looking to the parent, distraction, self-soothing), and these strategies proved equally effective for reducing negative affect over a three second period with each parent [4]. However, when comparing infants’ displays of negative affect to parental unresponsiveness across the 3, 5, and 7-month assessments, reductions in negative affect across that time period were only found for paternal unresponsiveness.…”
Section: Parent-partner As a Context Of Er Developmentmentioning
confidence: 99%